2016
DOI: 10.1149/2.0051612jes
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sorption Kinetics on Bare and Platinum-Modified Palladium Nanofilms, Grown by Electrochemical Atomic Layer Deposition (E-ALD)

Abstract: Nanofilms of Pd were grown using an electrochemical form of atomic layer deposition (E-ALD) on 100 nm evaporated Au films on glass. Multiple cycles of surface-limited redox replacement (SLRR) were used to grow deposits. Each SLRR involved the underpotential deposition (UPD) of a Cu atomic layer, followed by open circuit replacement via redox exchange with tetrachloropalladate, forming a Pd atomic layer: one E-ALD deposition cycle. That cycle was repeated in order to grow deposits of a desired thickness. 5 cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Studies of E-ALD have, thus far, primarily involved deposition on flat surfaces, , except for studies using SLRR, which was initially developed to coat the surfaces of nanoparticles with minimum quantities of catalytic metals. , The present study was undertaken to investigate similar deposits on the surfaces of three-dimensional materials in the form of submicron-sized powders. Such powders have applications in hydrogen separation, fuel cells, sensors, and catalysts. Prior work on hydrogen reactions with powders has involved both elemental and alloy powders. Powders typically allow for a much larger electrochemical surface area, for a given superficial surface area, compared with a planar substrate, increasing the rates of interfacial reactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of E-ALD have, thus far, primarily involved deposition on flat surfaces, , except for studies using SLRR, which was initially developed to coat the surfaces of nanoparticles with minimum quantities of catalytic metals. , The present study was undertaken to investigate similar deposits on the surfaces of three-dimensional materials in the form of submicron-sized powders. Such powders have applications in hydrogen separation, fuel cells, sensors, and catalysts. Prior work on hydrogen reactions with powders has involved both elemental and alloy powders. Powders typically allow for a much larger electrochemical surface area, for a given superficial surface area, compared with a planar substrate, increasing the rates of interfacial reactions .…”
Section: Introductionmentioning
confidence: 99%
“…SLRR on nanoparticles was previously demonstrated by Pt deposition on Au nanoparticles for oxygen reduction. 18 Previous work has shown that modification of the surface of a Pd nanofilm with Rh 19 or Pt 20,21 using E-ALD resulted in enhanced rates for H absorption and desorption. This is expected because of a less stable surface hydride on Rh or Pt, as compared with Pd.…”
Section: Introductionmentioning
confidence: 99%
“…In study of Zhao, High-quality, ultrathin (∼2.2 nm) 2D PdSe 2 flakes are achieved on mica substrates through a NaCl-assisted ambientpressure CVD [133]. Stickney grew nanofilms of Pd using an electrochemical form of ALD (E-ALD) on 100 nm evaporated Au films on glass [134]. Jacques Rozière discuss the electrodeposition of two-dimensional (2D) Pt-nanostructures on Highly Oriented Pyrolytic Graphite (HOPG) achieved under constant applied potential versus a Pt counter electrode [135].…”
Section: Surface Deposition Methodsmentioning
confidence: 99%
“…Another supporting factor is that Pt has a higher work function compared to Pd [109]. Finally, the extra Pt in the deposit could also be due to the slightly faster displacement kinetics between Pt and H atoms as compared to that of the competing Pd counterpart [110,111]. The analysis of all XPS composition characterization results suggest that the solution composition ratio between Pt and Pd chloride complexes could still be used for relatively accurate control of the Pt:Pd ratio in large compositional range of alloy films deposited by SLRR of H upd .…”
Section: Compositional Characterization By Xpsmentioning
confidence: 99%